SEISMOGRAVITATIONAL OSCILLATIONS OF THE EARTH AND ASSOCIATED DISTURBANCES OF THE ATMOSPHERE - Lin'kov Ye.M.; Petrova L.N.; Zuroshvili D.D. (My University, 1989)
Seismogravitational oscillations are movements of the earth in which inertial and gravitational accelerations of similar magnitude are generated on its surface. These include the lowest-frequency characteristic oscillations of the earth, especially the 0S2 mode, as well as the ultralong-period oscillations. Characteristic oscillations and earth tides have now been studied fully, theoretically and observationally. But detailed studies of the new phenomenon of seismogravitational oscillations with periods from 1 to 4 hours have been made only recently, by seismologists at Leningrad. The phenomenon occurs in the absence of strong earthquakes and exhibits a stable spectrum. Information on this new phenomenon and associated processes in the atmosphere and ocean will be useful in understanding the interaction of the earth shells, improving our knowledge of its deep structure, and determining what role seismogravitational oscillations may play in triggering of earthquakes.